Analysis of the Effect of Service Quality on Consumer Satisfaction and Loyalty - Emeritus G. Bitros; Syahwami; Iswahyu Pranawukir; Mohamad Ghozali; Hamirul (International Journal of Economics (IJEC), 2024)
This research aims to provide an analysis of the influence of service quality which is correlated with customer satisfaction and loyalty. The influence of customer satisfaction on customer loyalty has a very important role in customer satisfaction and customer loyalty. This research was conducted at Warmindo Maharasa, Yogyakarta which has a population of all Warmindo customers who have visited with a population sample with a total of around 100 respondents. The calculation of the number of indicators will be multiplied by 5 to 10. The data collection process was carried out using a questionnaire method and also a Likert scale as a way of measuring the 21 indicators contained in the 3 research variables. The data analysis technique in this research uses path analysis. The results of this research show that service quality has a positive and significant influence on customer loyalty. Likewise, service quality has a positive and significant role in customer satisfaction. Then customer satisfaction presents a positive and significant element in customer loyalty. The results of this research also show that customer satisfaction influences service quality on customer loyalty.